2013
DOI: 10.1371/journal.pone.0065953
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Approach for Virus Detection in Skin Lesions

Abstract: To assess presence of virus DNA in skin lesions, swab samples from 82 squamous cell carcinomas of the skin (SCCs), 60 actinic keratoses (AKs), paraffin-embedded biopsies from 28 SCCs and 72 kerathoacanthomas (KAs) and fresh-frozen biopsies from 92 KAs, 85 SCCs and 92 AKs were analyzed by high throughput sequencing (HTS) using 454 or Ion Torrent technology. We found total of 4,284 viral reads, out of which 4,168 were Human Papillomavirus (HPV)-related, belonging to 15 known (HPV8, HPV12, HPV20, HPV36, HPV38, HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 51 publications
(67 reference statements)
2
89
0
1
Order By: Relevance
“…Compared to previous analysis of the same sample pool using 454GSFLX and Ion Torrent PGM technologies13, we obtained a 260-fold and 35-fold larger number of viral reads using the Illumina MiSeq, respectively. The MiSeq analysis detected 26 established or putative HPV types, compared to 7 and 14 detected by GSFLX and PGM, respectively.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Compared to previous analysis of the same sample pool using 454GSFLX and Ion Torrent PGM technologies13, we obtained a 260-fold and 35-fold larger number of viral reads using the Illumina MiSeq, respectively. The MiSeq analysis detected 26 established or putative HPV types, compared to 7 and 14 detected by GSFLX and PGM, respectively.…”
Section: Resultsmentioning
confidence: 76%
“…In the pool with 142 skin samples amplified only with whole genome amplification (but not with prior PCR), the deeper Illumina sequencing resulted in 200 times and 25 times more total number of reads compared to previous metagenomic sequencing using 454 and Ion Torrent technologies13 and generated 260 times and 35 times more number of viral sequences as well as 4 times and 2 times more HPV types, respectively. 3 previously unknown putative HPV types were only found using the Illumina technology and for one of them almost the complete sequence was obtained.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Next-generation high-throughput sequencing (HTS) is emerging as an improved means to survey human disease origins and progression,16,17 as decreasing cost and increasing throughput make this approach an attractive compliment to traditional diagnostics. For example, one investigation used HTS to analyze human skin lesions and found that 97% of the virus sequences corresponded to human papillomavirus (HPV) 16. These results are consistent with the biological context of the study, as HPV is known to infect keratinocytes in mucosa or skin and can elicit a wide range of diseases from benign lesions to invasive tumors.…”
mentioning
confidence: 99%
“…The targeted nature of these methodologies inhibit their ability to accommodate the true diversity of human pathogens in a clinical specimen, especially viruses [1]. Next generation sequencing (NGS) technologies are quickly demonstrating their ability to provide broad detection of infectious agents in a target-independent manner [2-7]. NGS has many advantages beyond the improved detection of all suspected, unsuspected, or even novel pathogens in a clinical specimen [8].…”
Section: Introductionmentioning
confidence: 99%